Boiler Efficiency Analysis with Indirect Method PT. Indonesia Power UBP PLTU Lontar Unit 2 - Pamungkas, Candra Nur; Hidayati, Noor; Abadi, Cecep Selamet (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
Boiler efficiency is one of the important factors in determining the performance and environmental sustainability of PLTU. This study aims to analyze the factors that cause a decrease in boiler efficiency unit 2 PLTU Lontar. This study uses the indirect method (heat losses), it is found that the efficiency is 81.05%, and several large heat losses are found, namely L2: losses due to moisture content in coal of 5.01%, L3: losses due to hydrogen content in coal of 6.92% and comparison of heat losses data of PLTU Lontar boiler in 2015 and 2024. The analysis shows that the efficiency of the Lontar PLTU boiler has decreased from 82.96% in 2015 to 81.05% in 2024. This decrease is caused by several factors, namely: Increase in L3 (loss due to hydrogen content in coal) and L5 (loss due to unburned carbon).Decrease in L9 (loss due to sensible heat in fly ash).Decrease in coal quality. Efforts to improve boiler efficiency need to be made, such as, maintaining coal quality is very important to maintain boiler efficiency, and conducting regular boiler maintenance. The implementation of these measures is expected to improve the boiler efficiency of PLTU Lontar, reduce pollutant emissions, and improve environmental sustainability